Development and application of a robotic coal analysis system for process control in coal preparation - Qi LIU; Yu LIANG; Hong ZHANG; Mingxing WANG; Bao ZONG; Kun YANG; Jinxiang ZHAO; Junwei PEI; Feng ZHANG; Ying LIN (Meitan kexue jishu, 2025)
Coal preparation plants are a crucial component of intelligent coal mining operations, where the accuracy and speed of coal quality analysis directly influence the precision and timeliness of production control adjustments. Therefore, achieving high-precision and rapid testing of production coal samples is fundamental to refined coal preparation. The key factors affecting the ashing rate of coal samples are investigated, and an optimized approach using oxygen-enriched combustion technology for ash content determination is proposed. The research demonstrates that when the oxygen flow rate in a muffle furnace exceeds 3 L/min, the test results are consistent with national standards, reducing the measurement time from 40 minutes to 10 minutes, with a maximum repeatability error of no more than 0.20%. Additionally, a UV sulfur analyzer was developed, addressing the challenges posed by coulometric and infrared sulfur analyzers, providing accurate results with simple operation. To further enhance the intelligence level of coal preparation plants, robotic laboratory technology was applied to production control coal quality testing, with the development of an inverted robot layout and a non-opening sample weighing technique, enabling fully automated detection and data transmission of ash content, total sulfur content, and total moisture. A comparative analysis between robotic and manual testing showed that the precision and accuracy of the robotic tests were within the limits permitted by national standards. The research outcomes contribute significantly to the intelligent development of coal quality testing in coal preparation plants and hold great significance for advancing intelligent coal mining and refined coal preparation.